PENYELESAIAN TINDAK PIDANA PENGANIAYAAN MELALUI PROSESI MANDOA PERDAMAIAN DI DESA KETAPING JAYA KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI - Jodi Saputra; Mukhlis R; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research is related to the settlement of criminal acts of persecution through a peace prayerprocession in Ketaping Jaya Village, Inuman District, Kuantan Singingi Regency. Settlement of problemsbetween perpetrators and victims of criminal acts of persecution is not only resolved in the criminaljustice system as a formal settlement, but in the community the settlement through customary law, namelythe peace prayer procession, can be a solution or way of resolving criminal acts of persecution. Thereforeit is necessary to study, first, the process of resolving the crime of persecution through a peace prayerprocession, as well as the impact of this settlement on the level of crime in Ketaping Jaya Village, InumanDistrict, Kuantan Singingi Regency, secondly the influence of the mechanism for solving the crime ofpersecution through the peace prayer process on recidivists in reducing/preventing criminal acts ofpersecution.This research is a sociological law research, because it is based on field research, namely bycollecting data from observation, interviews, and literature studies that have to do with problems usingqualitative data analysis, producing descriptive data, and concluded with a deductive thinking method.From the results of the study, it was concluded that, first, the settlement of the crime ofpersecution through a peace prayer procession in Ketaping Jaya Village, Inuman District was effective,because the settlement had a positive impact on reducing crime rates in Ketaping Jaya Village. However,there are still weaknesses, namely the settlement process takes quite a long time because the partiesinvolved, especially the ninik mamak of both parties, can delay the predetermined settlement time forpersonal reasons and unilaterally. Second, the completion of the crime of persecution through the peaceprayer procession greatly influences the recidivist in reducing or preventing the crime of persecution. Inaddition, this settlement also affected the behavior of the perpetrators and the surrounding community,which became better than before due to fear of sanctions, be it fines or social sanctions.Keywords: Customary Law-Persecution-Prayer for Peace-Recidivist